Holding Point and Holding Pattern Feasibility Test for Training and Initial Approach Procedure - Zepa, Giga Valtian; Fajril, Almeyda Iftitach; Wicaksono, Agung Wahyu (PT FORMOSA CENDEKIA GLOBAL, 2025)
Holding pattern is an aircraft maneuver to remain in the air within a certain period to delay movement. This research aims to ascertain whether the creation of certain holding points used specificially for holding patterns exercises. This research uses the Research & Development (RnD) method which involves the process of planning, technical design, and feasibility test using Cessna 172Sp aircrafts. The results showed that the holding point could be carried out at the coordinates of the holding point coordinates 8°20'59